A study of unity and patriotism elements in film Ola Bola: a thematic analysis / Nurul Asyikin Deraman and Fariza Hanis Abdul Razak - Deraman, Nurul Asyikin; Abdul Razak, Fariza Hanis (Centre for Media and Information Warfare Studies, Faculty of Communication and Media Studies, Universiti Teknologi Mara, Malaysia, 2018)
Malaysia is a multiracial country that required Malaysian to understand each other’s religion and culture in order to maintain the peace of the country. Hence, the research purpose is to identify the elements of patriotism and unity that’s been portrayed in Ola Bola film. Using film as a way to propagate the patriotism and unity among Malaysian is not a new thing as Malaysian films such as Sepet, Gubra, Talentime and Estet are some films that brings all races in Malaysia under one roof. In addition, the film is said to play vital role in uniting people and also as a good platform to inject the patriotic elements among Malaysian as people tend to imitate what they see and hear from a film. A focus on patriotic film to inject patriotism is important so that Malaysian love and loyal to country endlessly. Plus, unifying elements create harmony and brings people together instead of dividing them by race, culture, political beliefs or other differences.